Writer's resources : - Robitaille, Julie (Thomson / Heinle, 2002)
The best way to learn to write well is through the use of clear examples and abundant practice. WRITER'S RESOURCES: FROM PARAGRAPH TO ESSAY helps develop students' confidence and skills as writers by presenting concepts in simple, clear fashion, and reinforcing them with numerous student peer examples and frequent practice exercises that allow students the opportunity to apply what they have learned. Using four student peers who share their advice and examples of writing throughout the book, this paragraph-to-essay level text teaches students the fundamentals of the writing process, including paragraph and essay structure and development and rhetorical patterns. The authors impart the essentials of grammar and mechanics by providing the kind of peer encouragement and supportive learning environment that will help your students take the risks necessary to become better writers. Along with a myriad of additional exercises and activities on the available Writer's Resources CD-ROM and the web-based learning system CengageNOW, WRITER'S RESOURCES: FROM PARAGRAPH TO ESSAY will help your students improve their writing and develop their own distinct writer's voice.